Characteristic of Leaf Peltate Glandular Trichomes and Their Variability of Some Lamiaceae Martinov Family Species - Svidenko, Lyudmyla; Grygorieva, Olga; Vergun, Olena; Hudz, Natalia; Horčinová Sedláčková, Vladimíra; Šimková, Jana; Brindza, Ján (Agrobiodiversity for Improving Nutrition, Health and Life Quality, 2018)
Glandular trichomes are important taxonomic characters in the Lamiaceae family. The objects of our investigations were plants of Lamiaceae family collected from the experimental base of Institute of Rice of the National Academy of Agrarian Sciences (Plodove, Ukraine). Fresh leaves were collected for the morphological analyse. The dimensions of glands (diameter in µm) were measured using of macroscope Discovery V12 Carl Zeiss at the Institute of Biodiversity Conservation and Biosafety of the Slovak University of Agriculture in Nitra (Slovakia). Peltate glandular trichomes with essential oil are localized on the adaxial and abaxial leaf surfaces. Their size on the adaxial and abaxial leaf sides is different. The diameter of trichomes on the adaxial and abaxial side of leaves was 65.70 and 61.41 (Nepeta transcaucasica Grossh.), 70.10 and 74.54 (Salvia officinalis L.), 72.02 and 67.39 (Monarda fistulosa L.), 80.53 and 85.11 (Ocimum basilicum L.), 94.35 and 105.12 (Satureja montana L.), 95.11 and 60.37 (Thymus serpyllum L.), 96.48 and 90.57 (Thymus vulgaris L.), 106.88 and 107.69 (Hyssopus officinalis L.), 110.61 and 88.22 (Hyssopus angustifolius Bieb.), respectively. It was noted that the leaf adaxial side of Salvia sclarea L. had no glandular trichomes of lamiaceous type at all but on an abaxial side of leaves only with the diameter 96.47 μm. The tested plant species showed significant differences in size and colour of peltate glandular trichomes producing essential oils. This difference can be used during macroscopic analysis of herbal substances. Aromatic plants that were grown in Steppe zone of South Ukraine are perspective plants because of presence a well-generated excretory system which contains essential oils.